(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
Various medical conditions can influence how the body interacts with trace elements, resulting in either deficiencies or toxicities that may play a role in the onset of diseases and pathological conditions. Consequently, proper management of trace element imbalances necessitates a comprehensive evaluation of an individual’s trace element levels. Therefore, this study assessed the levels of some trace elements and haematological indices in sickle cell patients. Fifty-eight (58) adults, twenty-nine of whom were sickle cell patients attending the haematology clinic at Federal Medical Centre (FMC) Abakaliki, Ebonyi State, and 29 apparently healthy controls, mainly staff at the facility who had consented to participate, were recruited into the study. Trace elements zinc, selenium, manganese, iron, and cobalt, and haematological indices PCV, MCH, and reticulocytes were determined using standard procedures. Plasma Zn and Fe, as well as Hb, PCV, and MCH, reported for sickle cell patients, were significantly (p<0.05) lower than those reported for their control counterparts. A contrary observation was made on manganese, while the value reported for cobalt was the same in the two groups. In conclusion, it was deduced from this study that trace elements and haematological indices are greatly reduced in the sickle cell condition.